Identification of the sex-linked region of Siniperca scherzeri and development of sex-specific markers - Yang Li; Yu Cui; Xiaojun Ye; Maoyuan Wang; Hao Xu; Yannian Wu; Jian Jin; Honggui Huang; Mingyong Lai; Zhiyong Wang; Dongling Zhang (Aquaculture, 2025)

Identification of Increased Grain Length 1 (IGL1), a novel gene encoded by a major QTL for modulating grain length in rice - Jiayu Niu; Fei Wang; Chengcheng Yang; Qiwen Ye; Jingxian Huang; Yumei La; Qianqian Wang; Jie Dai; Tiange Hu; Liran Sang; Peijiang Zhang; Yu Zou; et al. (Theoretical and Applied Genetics, 2024)

Comparison of Growth Performance and Muscle Nutrition Levels of Juvenile Siniperca scherzeri Fed on an Iced Trash Fish Diet and a Formulated Diet - Maoyuan Wang; Mingyong Lai; Tian Tian; Meiying Wu; Yinhua Liu; Ping Liang; Liuting Huang; Zhiqing Qin; Xiaojun Ye; Wei Xiao; Honggui Huang (Fishes, 2023)
To assess the possibility of using a formulated diet instead of an iced trash fish diet for feeding spotted mandarin fish (Siniperca scherzeri), a 20-week feeding trial was conducted. The objective of the study was to examine the effects of the formulated diet (FG) and the iced trash fish diet (XG) on the growth performance and muscle nutrient composition of the fish. The results showed that the spotted mandarin fish fed with an XG had slightly higher survival rates, weight gain rate, fullness, hepatic index, and viscera index compared to those fed with an FG, although the differences were not significant (p > 0.05). Additionally, in terms of muscle composition, the FG group had higher levels of crude protein and ash content in the fish muscle compared to the XG group (p

Selenium Deficiency Induces Inflammation via the iNOS/NF-κB Pathway in the Brain of Pigs - Yilei Zhang; Jiawen Cui; Yingfei Lu; Chunzheng Huang; Honggui Liu; Shiwen Xu (Biological Trace Element Research, 2020)

Transformation of upland rice with the bar gene and selection for resistance to the herbicide Basta - Xiaowei Tian; Jianqin Hao; Biao Fang; Pengpeng Geng; Honggui La; Danian Huang; Huaqi Wang (Euphytica, 2015)